Honda Vario 125 Engine Modification Performance Analysis - Bahtiar Wilantara; Zaky Kurniawan; Muhammad Andre (Politeknik Piksi Ganesha Indonesia, 2025)
This study aims to describe the performance of the Honda Vario 125 engine that has undergone modifications to five main components, namely the piston, valve, camshaft, throttle body, and injector. Performance measurements were carried out to determine changes in torque and horsepower after the modifications were applied. The research method used was a quantitative descriptive approach with testing using a dyno test. The test procedure included engine preparation, tool calibration, and the implementation of a full dyno test from idle to maximum speed. The results showed that the engine was capable of producing a maximum torque of 31.36 N m at 3,507 rpm and a maximum power of 20.21 HP at 7,693 rpm. These values ​​indicate an increase in the engine's ability to produce power and thrust at certain speeds. Overall, this study provides an empirical description of the performance characteristics of the Honda Vario 125 engine after mechanical modifications